2020
DOI: 10.1002/ange.201906823
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschallaktivierte Sensibilisatoren

Abstract: Durch Licht ausgelöste Verfahren in der Krebstherapie sind üblicherweise durch ihre geringe Penetrationstiefe limitiert. Die Sonotheranostika, insbesondere die sonodynamische Therapie (SDT), die sich von der photodynamischen Therapie (PDT) unterscheidet und hoch penetrierende Schallwellen zur Aktivierung einer Klasse von schallresponsiven Materialien verwendet, die als Sonosensibilisatoren bezeichnet werden, hat in den letzten Jahren an erheblichem Interesse gewonnen. Der Effekt der SDT hängt eng mit den struk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 192 publications
(164 reference statements)
0
4
0
Order By: Relevance
“…The high triplet state quantum yield and inhibition of energy dissipation through non-radiative pathways would be the key factors to improve the 1 O 2 generation efficiency of the metal NCs. Since water-soluble thiolated metal NCs have multifunctionality such as imaging, drug delivery, and multiple sensitizing capability (photo-sensitizer, radiosensitizer, and sonosensitizer), it would be useful as a multipurpose ROS mediated nanomedicine 84,85,149,150 (6) Regarding the in vivo PDT applications, the use of specic ligands for metal NCs increases the selectivity toward the target (e.g., cancerous tumors), an approach called "active targeting". Targeting ligands on metal NCs are responsible for the selective interaction between the metal NCs and specic receptors on the surface of tumor cells, but not healthy cells, thus increasing the internalization of the NCs.…”
Section: Discussionmentioning
confidence: 99%
“…The high triplet state quantum yield and inhibition of energy dissipation through non-radiative pathways would be the key factors to improve the 1 O 2 generation efficiency of the metal NCs. Since water-soluble thiolated metal NCs have multifunctionality such as imaging, drug delivery, and multiple sensitizing capability (photo-sensitizer, radiosensitizer, and sonosensitizer), it would be useful as a multipurpose ROS mediated nanomedicine 84,85,149,150 (6) Regarding the in vivo PDT applications, the use of specic ligands for metal NCs increases the selectivity toward the target (e.g., cancerous tumors), an approach called "active targeting". Targeting ligands on metal NCs are responsible for the selective interaction between the metal NCs and specic receptors on the surface of tumor cells, but not healthy cells, thus increasing the internalization of the NCs.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 For these reasons, ultrasound has become a key diagnostic tool in the clinic. 19 Moreover, recent research has indicated ultrasound as an effective alternative to light to trigger ROS production or release of small molecules by a process called sonodynamic therapy (SDT). 20,21 Considering the above advantages of ultrasound, the development of novel and dual-action sonosensitizers that on ultrasound stimulation can simultaneously release CO and produce ROS for cancer therapy will be a significant milestone in cancer research and is yet to be developed.…”
mentioning
confidence: 99%
“…[263] A deeper penetration depth of tumor tissues can be realized by ultrasound. [264] Zhang and coworkers designed nanodroplets (IR780NDs) for SDT based on IR780. [65] Under the action of mechanical wave ultrasound radiation and IR780 with mitochondriatar geting ability, IR780NDs targeted mitochondria and produced excessive ROS to induce apoptosis of 4T1 cells.…”
Section: Sonodynamic Therapymentioning
confidence: 99%